Alain Badiou. Theatre and politics as collective subjectivations - Vinolo, Stephane (Estudios de Filosofía, 2018)
Since the Greek emergence of philosophy, theatre and politics maintained complicated but close links. In their own way, both seek to unify multiplicities through the localized interweaving of ideas and bodies. Overcoming the Platonic, Aristotelian and Heideggerian models of the relationship between art and philosophy, it is shown with Badiou that the contemporary articulation of theatre and politics lies within a dialectical game that constitutes the collective Subject of both elds. For this purpose, it is necessary to rethink the point of contact between theatre and politics in the light of their different production of truths. Relocating the truth at the centre of both activities, it is possible to unveil with Badiou that both contemporary theatre and politics contribute to the creation of faithful Subjects when the collective is built through the indifference to the differences. Thus, beyond the fact that theatre and politics can be objects of one another, and that they inhabit each other, theatre reveals what can still be, today, the only real and true politics.